Rhizopus sp.2000 FM – the active fungi exolipase producer - Borisenko, A.; Antoniuk, Maria; Eisenberg, Victoria; Kapichon, A.; Stoiko, V. (My University, 2009)
The experimental results support the fact that the sunflower oil is the effective inductor of exolipase biosynthesis. The high values of LA demonstrated on the medium with sucrose and starch addition are exponents of the physiological and biochemical properties of the strain Rhizopus sp. 2000 FM. Maximal activity is registered for the substrate with addition of the 1% sunflower oil. Further increase of this oil caused the decrease of the fermentative activity, thus, one could consider the sunflower oil to be not only the inductor but also the represser of the lipase biosynthesis. What concerns the growth and biomass accumulation we could state that the addition of the significant quantity of the sunflower oil, stimulates the growth of the micromycete Rhizopus sp. 2000 FM. The data on the growth rate and LA of the fungus strain Rhizopus sp. 2000 FM on the carbon sources, along with the detection of other components of the medium, is believed to support the optimization the content of the nutritive medium for the cultivation of the new active exolipase producent — fungus Rhizopus sp. 2000 FM.
Keywords: продуцент; Rhizopus; екзоліпаза; Rhizopus; экзолипаза; producent; Rhizopus; exolipase; кафедра біотехнології і мікробіології